Загальні принципи вивчення глобалізаційних процесів у межах сучасної культурології - Пилявець, Л.С. (Культура народов Причерноморья, 2013)
У статті визначено загальні теоретико-методологічні принципи вивчення глобалізаційних
процесів. Зокрема, загальнонаукові - системності, об’єктивності, всебічності та інші. Досліджено
специфічні принципи детермінізму, ідентифікації, толерантності та інші. Велика увага приділена
типам глобалізаційних процесів. Акцентується увага на їх характеристиці крізь призму
культурологічної методології дослідження. В статье определены общие теоретико-методологические принципы изучения
глобализационных процессов. В частности: общенаучные - системности, объективности,
всесторонности и т.д. Исследовано специфические принципы детерминизма, идентификации,
толерантности и т.д. Большое внимание уделено типам глобализационных процессов. Акцентируется
внимание на их характеристике с позиций современной культурологической методологии исследования. The article outlines the methodological principles study of globalization, including the following
general scientific as consistency, objectivity, comprehensiveness, etc., and specific as determinism, identity,
tolerance, etc., and found globalization types of processes and their general characteristics.
Thus, the article noted that consideration of globalization as a multidimensional, multivariate, multidimensional
process due to the fact that economists, politicians, sociologists, cultural historians and philosophers, thinking
about unprecedented changes in the world, sees the cause of globalization, features of interference and which
require systematic knowledge of various sciences of globalization on an interdisciplinary level.
However, the author emphasized that, despite the large number of papers on globalization at present no
theoretical attempts to summarize empirical facts, their constructive and critical interpretation and systematic
and holistic consideration of the possibility of studying globalization trends.
Therefore, Article globalization is seen as the only multi- process based on a combination of interdisciplinary
approaches, according to the author, to avoid unilateral, schematic analysis of globalization without concrete
reality, and explain their difficulties by laws inherent in simpler phenomena.
Reveals the importance of methodology as the application of general principles and theories in solving research
problems and issues specific science. All principles which can be applied in the study of globalization, the author
divides into general scientific, which have counterparts in different scientific areas, as well as specific cultural
principles that apply within a particular section in cultural studies. In particular, the principles such as
consistency, objectivity, comprehensiveness, etc., and specific as determinism, identity, tolerance and so on.
The author states that this variety of methods inevitably gives rise to the problem of selecting the most
appropriate and promising to solve this or that doctrine of specific research tasks. From this choice depends
largely on the effectiveness and practical importance of the theoretical conclusions of any science, including
cultural studies.
Based on established principles, the author presents a typology of globalization processes and their general
characteristics. Thus, an important characteristic of globalization as the author considers their historical
specificity, according to which the processes are divided into unique, that is, which never happened in history,
and cyclic, providing periodic changing nature of relations.
Signs classification globalization by isolates referred to historical specificity, structure determination, dynamics,
controllability, the impact of the transformation of the scale values, the spread, a measure of influence on the
course of other processes, the impact and consequences.
Thus, the author defines globalization as a unique, non-linear (in particular, network) strongly dynamic,
spontaneous and generally irreversible process.
In conclusion the author noted that methodological study of the phenomenon of globalization as a whole can be
best accomplished within a theory of culture as a field of knowledge that can be used as a strategy for individual
scientific disciplines and interdisciplinary areas of study globalization. As mentioned principles identified in the
study of globalization author points out that they can not be overemphasized: without them the study of
globalization, like any social and cultural phenomenon, has no methodological support.
However, the article noted that the above types of globalization are not intended to be exhaustive and may be
supplemented and expanded as consideration process should be approached with varying degrees of accuracy,
in addition, tasks may vary, but knowledge is constantly evolving. This typology, as specified by combining
together the identified types of processes or supplement them where necessary new or specification of this
typology in a certain direction, can be fruitful for further study and globalization. This should take into account
the dialectic of globalization and determinism, and the fact that due to the trend towards globalization of society
any change, becoming global, affecting the entire social system as a whole.